Pain Assessment in Hospitalized Older Adults With Dementia and Delirium - Paulson, Christina May; Monroe, Todd; Mion, Lorraine C. (Journal of Gerontological Nursing, 2014)
Pain can have negative effects leading to prolonged hospital stays. Determining the presence of uncontrolled and untreated pain in patients with cognitive impairments such as delirium, dementia, and delirium superimposed on dementia (DSD) is challenging. One tool commonly suggested for use in assessment of pain in older adults with cognitive impairment is the Pain Assessment In Advanced Dementia (PAINAD) scale. Proper use of the PAINAD scale as part of a comprehensive pain management plan can help reduce the likelihood of a patient experiencing unrecognized and untreated pain. Using an individual example, this article illustrates best practices in pain assessment and management for a woman experiencing DSD during an acute hospitalization. [ Journal of Gerontological Nursing, 40 (6), 10–15.]